The Internet As A Sales Channel In Asia A Study On The Challenges Faced By A Global Express Company In An Emerging Digital Economy In Asia - Aun, Lee Heng (2000)
The objective of this study was to access the potential of a Express company such as TNT using the internet as a sales channel in Asia, to compare TNT internet capabilities against its competitors.